How to Turn an Industry Green: Taxes versus Subsidies - Susanne Dröge; Philipp J. H. Schröder (Deutsches Institut für Wirtschaftsforschung (DIW), 2003)
Environmental policies frequently target the ratio of dirty to green output within the same industry. To achieve such targets the green sector may be subsidised or the dirty sector be taxed. This paper shows that in a monopolistic competition setting the two policy instruments have different welfare effects. For a strong green policy (a severe reduction of the dirty sector) a tax is the dominant instrument. For moderate policy targets, a subsidy will be superior (inferior) if the initial situation features a large (small) share of dirty output. These findings have implications for policies such as the Californian Zero Emission Bill or the EU Action Plan for Renewable Energy Sources.
Keywords: Q28; H2; L13; 330; Environmental policy; Monopolistic competition; Taxes; Subsidies; Welfare; Zero Emission Bill; Umweltabgabe; Umweltschutz; Subvention; Mehr-Sektoren-Modell; Monopolistischer Wettbewerb; Wohlfahrtseffekt; Theorie